Efficacy of dequalinium chloride vaginal tablets in treatment of bacterial vaginosis - A. B. Khuraseva; T. V. Reminnaya (Акушерство, гинекология и репродукция)
Aim: to evaluate the efficacy and duration of the therapeutic effect of dequalinium chloride (in comparison with clindamycin) in treatment of vaginal dysbiosis. Materials and methods. A total of 73 fertile-aged women (18-35 years old) with abnormal vaginal microbiota were examined. The patients were randomized into two groups: Group 1 (main) included 37 women receiving dequalinium chloride; Group 2 (control) included 36 women under clindamycin therapy. The efficacy was assessed by analyzing patients’ complaints, by gynecological examinations, pH values of the vaginal fluid, the Amsel criteria, the microscopy results and the polymerase chain reaction (PCR). Results. Before the treatment, the Amsel criteria were positive in 36 patients (97.29%) in the main group and in 31 patients (93.93%) in the control group; all patients showed an increase in the pH values of the vaginal fluid by more than 4.5 units. The state of vaginal microbiocenosis as evaluated with RT-PCR diagnostics (Femoflor 16 analysis) identified a variety of gram-positive and gram-negative bacteria with a marked decrease in the number of Lactobacilli. During the treatment period, there were no complaints of adverse events; pH values were normal in all patients; the Femoflor 16 analysis showed a significant decrease in the amounts of pathogenic microorganisms. As assessed in 1 month after the treatment, the therapeutic effect persisted. Conclusion. The dequalinium chloride has antibacterial effect on bacterial vaginosis. The results of the study showed that dequalinium chloride had the efficacy comparable with that of clindamycin.